Ventricular Tachycardia Induced by Weight Loss Pills - Manan Pareek; Nils Henrik Hansson; Erik Lerkevang Grove (Case Reports in Medicine, 2013)
A previously healthy 29-year-old man was admitted with palpitations, dizziness, and near-syncope after he had recently started taking weight loss pills purchased on the internet. The pills contained caffeine and ephedrine. An electrocardiogram and telemetry revealed multiple episodes of non-sustained monomorphic ventricular tachycardia, which was successfully treated with amiodarone. In conclusion, unauthorized weight loss pills can be harmful. In particular, ephedrine-containing drugs carry a risk of ventricular tachycardia and should be discouraged.